INFLUENCE OF THE MODEL SCALE ON HYDRODYNAMIC SCALING IN CFB BOILERS - Mirek,P. (2016)
Abstract The paper presents the results of experimental verification of the simplified set of scaling parameters for which the particle density as well as the cold model length scale may be chosen independently. The tests were carried out on two large scale 1/10 and 1/20 geometrically similar cold models of the Lagisza 966 MWth supercritical CFB boiler. The proposed set of dimensionless quantities allowed the Lagisza 966 MWth CFB boiler to be closely modeled by cold models. However, the agreement between the hot bed and cold model's suspension density distributions is better for the 1/10 scale cold model. That suggests that the choice of the scale of a cold model is not without effect on the macroscopic movements of solids in the riser. Moreover, the study shows that a simplification of the scaling laws which excludes the very important solid-to-gas density ratio can give acceptable results over a wide range of boiler loadings.